Managing early blight disease: hindrance to tomato fruit production - Singh, R K; Singh, Satyandra (Indian Horticulture, 2019)
Tomato is an easy and popular vegetable to grow but it is difficult to save its crop from disease and pests, because these are main hindrances in production of tomato. Early blight is second serious disease after tomato leaf curl virus disease. This is responsible for significant economic yield losses incurred in tomato production each year. Screening of early blight resistant tomato varieties/ lines is a single best approach for managing this disease.